Pre-service teachers' perceptions of preparedness for teaching practicum: a study of TESL undergraduates in selected Malaysian public universities / Mohd Amirul Atan - Atan, Mohd Amirul (2015)
The purpose of this study was to identify pre-service teachers’ perceived levels of preparedness for teaching practicum in terms of Pedagogical Content Knowledge (PCK) and Technological Pedagogical Content Knowledge (TPCK). The study also investigated the roles of the faculties in supporting pre-service teachers’ preparation for teaching practicum in terms of PCK and TPCK. Three groups of pre-service teachers attending Bachelor of Education in Teaching English as a Second Language (TESL) from three different public universities were purposefully selected to describe the development of their preparation for teaching practicum. A questionnaire survey form was used to identify the respondents’ level of preparedness for teaching practicum. Focused-group interviews were then conducted in each learning institution in order to gain in-depth information. The primary finding was that most of the respondents showed a high degree of preparedness for teaching practicum in terms of PCK and TPCK. The study also found that the pre-service teachers indicated that all the coursework in the program was primarily responsible for the development of their particular levels of PCK and TPCK. This finding also provided specific evidence that the technology courses thread in the program was integrated and interconnected throughout the program. The implications of the study towards teacher education programs as well as the pedagogical and policy aspects were also discussed. Future research recommendations are included for the investigation of actions the teacheppreparation program needs to take for improving on the different levels of pre-service teachers’ PCK and TPCK, the relationship of the cooperating teachers, university supervisors, and course instructors’ understanding of PCK and TPCK on the pre-service teachers’ TPCK development; and identification of significant relationships between pre-service teachers’ PCK and TPCK during the program and their use of technology in their future teaching career.